Is Fear of Failure a Psychological Barrier? An Empirical Study on Occupational Choices - Gürbüz, Fatma Gülruh; Ergun, Hande Sinem; Teraman, Seray Begüm Samur (My University, 2017)
In our age, “success” has been promoted as the ultimate aim and result in life. Failure has been underrated in our society. However, failure is important and necessary. The contradiction of success promoting mentality is that in order to be successful failure is essential. However, we do not come across failure stories as much as success stories. Success is nice and positive, but failure is unpleasant and most of the time is not welcomed by the society and our close relations. Therefore, managing failure is highly important and is not taught or mentioned anywhere. This study tries to show the possible connection between the Fear of Failure (henceforth FoF) and occupational choices by including wide range of career options (e.g. being a social entrepreneur, being an academician, being a paid employee either in a private company or public office, being self-employed/entrepreneur and being not working at all if it is possible). Methodology- Survey method is used as a research instrument and 413 university students accepted to be the part of the study. Multiple regression analyses were performed to test the proposed relationships. Findings- Among them only two models constructed with entrepreneurial intention and not working at all (if it is possible) was found significant. Conclusion-. Alongside different findings of the study, negative connotation attached to the FoF for entrepreneurial intentions are still valid.
Keywords: Fear; Failure; Fear of Failure; Occupational Choice; Entrepreneurial Intention